(3ZGjI GdeCehd aj TQM RHOI GdCUhds - (3GdHZOGOj GdcGXej, GdLhGO GdHZOGOj, LhGO Hf SYO Hf LhGO, J (B1065(3g`s ((3eMeO Hf gGOj GdfMhjs)
(3ChdgG (B:s
(3ef GdeSGFd GdJj de Ja HMdgG GdWGbI GdHTQjI(B... (3hSejJg HZGjI GdeCehd aj TQM RHOI GdCUhd(B...s
(3BNQgG (B:s
(3fLGfG Gddg hEjGce ef YbhHJg hCSHZ YdjfG Yeje aVdg hTGed QMeJgs
(3JHUQI GdYfhGf (B:s
(3RHOI GdCUhd ddHgGA GdYGedjs
(3JHUQI GdeDda (B:s
(3jYQa HGdaGVd GdLhGO, h(B: (3eMeO GdLhGOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L (B1(3, U(B510s
Keywords: (3CUhd Gdabgs